Identification of a Wheat-Psathyrostachys huashanica 7Ns Ditelosomic Addition Line Conferring Early Maturation by Cytological Analysis and Newly Developed Molecular and FISH Markers - Tan, Binwen; Zhao, Lei; Li, Lingyu; Zhang, Hao; Zhu, Wei; Xu, Lili; Wang, Yi; Zeng, Jian; Fan, Xing; Sha, Lina; Wu, Dandan; Cheng, Yiran; et al. (Frontiers in Plant Science, 2021)
Early maturation is an important objective in wheat breeding programs that could facilitate multiple-cropping systems, decrease disaster- and disease-related losses, ensure stable wheat production, and increase economic benefits. Exploitation of novel germplasm from wild relatives of wheat is an effective means of breeding for early maturity. Psathyrostachys huashanica Keng f. ex P. C. KUO (2n=2x=14, NsNs) is a promising source of useful genes for wheat genetic improvement. In this study, we characterized a novel wheat-P. huashanica line, DT23, derived from distant hybridization between common wheat and P. huashanica. Fluorescence in situ hybridization (FISH) and sequential genomic in situ hybridization (GISH) analyses indicated that DT23 is a stable wheat-P. huashanica ditelosomic addition line. FISH painting and PCR-based landmark unique gene markers analyses further revealed that DT23 is a wheat-P. huashanica 7Ns ditelosomic addition line. Observation of spike differentiation and the growth period revealed that DT23 exhibited earlier maturation than the wheat parents. This is the first report of new earliness per se (Eps) gene(s) probably associated with a group 7 chromosome of P. huashanica. Based on specific locus-amplified fragment sequencing technology, 45 new specific molecular markers and 19 specific FISH probes were developed for the P. huashanica 7Ns chromosome. Marker validation analyses revealed that two specific markers distinguished the Ns genome chromosomes of P. huashanica and the chromosomes of other wheat-related species. These newly developed FISH probes specifically detected Ns genome chromosomes of P. huashanica in the wheat background. The DT23 line will be useful for breeding early maturing wheat. The specific markers and FISH probes developed in this study can be used to detect and trace P. huashanica chromosomes and chromosomal segments carrying elite genes in diverse materials.